ChemInform Abstract: Stereoselective Aza‐Michael Addition of Anilines to 1‐Nitro Cyclohexene by Intramolecular Protonation. Issue 12 (March 2016) - Ghisu, Lorenza; Melis, Nicola; Secci, Francesco; Frongia, Angelo
Abstract: The title reaction proceeds with high stereoselectivity to form the corresponding trans‐products.